Radiographic features of oral manifestations of secondary hyperparathyroidism with cranial involvement: a rare case report - Guswan, I Nyoman; Priaminiarti, Menik; Saraswati, Inka; Julia, Vera (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2026)
Objectives: This case report aims to present a rare case of radiographic oral manifestations of secondary hyperparathyroidism associated with chronic kidney disease. Case Report: A 32-year-old female patient came to Universitas Indonesia Hospital with a chief complaint of gradual swelling in her oral cavity for approximately 1 year. Clinical examination revealed swelling in the gum and palate of the upper jaw, the swelling increasing in size, causing difficulty in speaking and eating. There is also face deformity along with the increasing size of the swelling.  The panoramic radiograph and MDCT showed thinning of cortical bone, absence of lamina dura, and ground-glass appearance in the dentomaxillofacial area, including several parts of the skull, which is consistent with characteristics of oral manifestations of secondary hyperparathyroidism (HPT). Conclusion: A rare case of secondary HPT associated with chronic renal illness that manifests with panoramic radiograph, MDCT, and oral characteristics is presented.